Una visión bentónica de arroyos y ríos pampeanos - Rodrigues Capítulo, Alberto (2004)
In this paper, Tributaries of the Río Paraná and Río de la Plata rivers (Arrecifes and Matanza-Riachuelo rivers, El Gato, El Pescado, Juan Blanco and Buriñigo streams). The System of Río Salado (Samborombón and Salado rivers, Las Garzas stream) and streams of Tandilia gills north-eastern slope stream (Napaleofú, Langueyú, Tandileofú, Chelforó and Vivoratá) were studied by analysing the zoobenthic community. Several streams tributaries of Rio de la Plata river are affected (to a different extent) by urban and industrial perturbations and they were compared with pristine streams of the region. Diversity and Biotic Indices were applied in the streams. Tolerant species and slow scores of the both indices were mainly registered in Matanza-Riachuelo river and El Gato stream, and the more sensitive taxa were identified in El Pescado and Juan Blanco streams. In Samborombon river there were salinity changes with taxa adapted to this condition (Polichaeta, Chasmagnatus granulata, Cyrtograpsus angulata, Cirripedia.